2014
DOI: 10.1159/000369487
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life under Capecitabine (Xeloda®) in Patients with Metastatic Breast Cancer: Data from a German Non-Interventional Surveillance Study

Abstract: Aim: This non-interventional surveillance study (NIS) collected data on the quality of life (QoL) of patients treated with capecitabine as mono- or combination chemotherapy in an outpatient setting. Methods: Capecitabine was administered orally for 14 days of each 21-day cycle. The main parameters of interest were QoL, compliance, patient and physician satisfaction, handling of hand-foot syndrome (HFS), and efficacy. The statistics were descriptive; some differences were compared using confidence intervals (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Recently the phase III study leading to the approval of Eribulin mesylate (eribulin), a novel microtubule dynamics inhibitor, as single agent in metastatic breast cancer, demonstrated that eribulin was not shown to be superior to capecitabine with regard to overall survival, progression-free survival or health-related quality of life [ 50 , 51 ]. Overall, although several novel drugs are currently available, capecitabine remains one of the most effective and used drugs in the treatment of metastatic breast cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the phase III study leading to the approval of Eribulin mesylate (eribulin), a novel microtubule dynamics inhibitor, as single agent in metastatic breast cancer, demonstrated that eribulin was not shown to be superior to capecitabine with regard to overall survival, progression-free survival or health-related quality of life [ 50 , 51 ]. Overall, although several novel drugs are currently available, capecitabine remains one of the most effective and used drugs in the treatment of metastatic breast cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capecitabine is widely considered to be a chemotherapy drug with manageable toxicity and a favorable risk:benefit profile in patients with MBC [ 25 , 26 ]. It is often used as a first-line treatment in older and frail patients to achieve disease control without significant side-effects [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial progress in improving diagnostic and therapeutic methods in recent years, breast cancer remains the second leading cause of cancer-associated mortality in women; and there were >500,000 mortalities in 2011 according to the World Health Organization statistics (2). Previous research suggests that recurrent metastasis in patients with breast cancer remains incurable and only 3% of cases can achieve complete remission for >5 years (3). The malignant biological behavior of breast cancer is regulated by multiple genes.…”
Section: Introductionmentioning
confidence: 99%